Visual integration across fixation: automatic processes are split but conscious processes remain unified in the split-brain - Pinto, Yair; Villa, Maria-Chiara; Siliquini, Sabrina; Polonara, Gabriele; Passamonti, Claudia; Lattanzi, Simona; Foschi, Nicoletta; Fabri, Mara; de Haan, Edward H. F. (Frontiers in Human Neuroscience, 2023)
The classic view holds that when 'split-brain' patients are presented with an object in the right visual field, they will correctly identify it verbally and with the right hand. However, when the object is presented in the left visual field, the patient verbally states that he saw nothing but nevertheless identifies it accurately with the left hand. This interaction suggests that perception, recognition and responding are separated in the two isolated hemispheres.However, there is now accumulating evidence that this interaction is not absolute; for instance, split-brain patients are able to detect and localise stimuli anywhere in the visual field verbally and with either hand. In this study we set out to explore this cross-hemifield interaction in more detail with the split-brain patient DDC and carried out two experiments. First, we looked at the confidence that DDC has in his responses. The experiment involved a simultaneous 'same' versus 'different' matching task with two shapes presented either within one hemifield or across fixation. The results showed that we replicated the observation that split brain patients cannot match across fixation, but more interesting, that DDC was very confident in the across-fixation condition while performing at chance-level. On the basis of this result, we hypothesised a two-route explanation. In healthy subjects, the visual information from the two hemifields is integrated in an automatic, unconscious fashion via the intact splenium, and this route has been severed in DDC. However, we know from previous experiments that some transfer of information remains possible. We proposed that this second route (perhaps less visual; more symbolic) may become apparent when he is forced to use a deliberate, consciously controlled approach. In an experiment where he is informed, by a second stimulus presented in one hemifield, what to do with the first stimulus that was presented in the same or the opposite hemifield, we showed that there was indeed interhemispheric transfer of information. We suggest that this two-route model may help in clarifying some of the controversial issues in split-brain research.